Academic Leadership in the Time of COVID-19—Experiences and Perspectives - Dumulescu, Daniela; Muţiu, Alexandra Ileana (Frontiers in Psychology, 2021)
The COVID-19 pandemic has been a sharp reminder that large scale, unpredictable events always bring about profound changes with significant consequences on many levels. In light of lockdown measures taken in many countries across the world to control the spread of the virus, academics were ‘forced’ to adapt and move to online settings all teaching, mentoring, research, and support activities. Academic leaders in higher education had to made decisions and to act quickly how were they to manage large educational communities, addressing students’, teachers’, and staff’s needs, as well as society’s needs. Using an inductive approach, our study seeks to highlight the main challenges faced by university leaders and to understand their responses to those challenges. The current study aims to investigate perceptions and experiences of academic leaders in a University in Romania during the COVID-19 pandemic. Our foci were the processes underlying their leadership decisions and actions during the second part of the 2019-2020 academic year. Data was collected through semi-structured interviews with 11 university and faculty leaders in Babeș-Bolyai University, Romania. The findings from the thematic analysis revealed three main themes emerging from participants’ responses: “the leader’s personal attributes”, “unity through decentralization” and “opportunities to reinvent the university.” Good practices to manage academic institutions in times of crises and changes are discussed, along with insights into strategies for supporting higher education development during crisis and post-crisis times resulting into recommendations for increasing management effectiveness.